RECURRENT LARYNGEAL NERVE INJURY: AN EXPERIENCE WITH 310 THYROIDECTOMIES - Chaudhary, Ishtiaq Ahmed; ullah, Sami; Masood, Rehan; Majrooh, Muhammad Ashraf; Mallhi, Ashraf Ali (Journal of Ayub Medical College Abbottabad, 2007)
Background: Thyroid surgery has been associated with complications ranging from nerve injury to death. Improvements in techniques have reduced the mortality rate to minimum. Morbidity, however, remains a significant concern. This study was designed to determine the prevalence of recurrent laryngeal nerve (RLN) injury and duration of recovery following transient recurrent laryngeal nerve injury, during thyroid surgery. Methods: This prospective, observational study was carried out in the Surgical Department of Fauji Foundation Hospital, Rawalpindi, from January 2000 to December 2005. All patients undergoing Thyroid surgery were included. Results: 310 patients, predominantly female (97.09%), were operated. Majority were euthyroid (90.33%). 3.22% patients had recurrent laryngeal nerve injury. Amongst them, 87.5% had transient and 12.5% had permanent nerve lesion. Majority of the patients (87.5%) showed signs of recovery within 12 weeks after surgery. Injury was observed more in huge goiters (3.57% transient and 1.42% permanent), total thyroidectomy (7.69% transient and 3.84% permanent) and during lobectomy and total thyroidectomy (6.25% respectively for transient and permanent nerve injury. Conclusion: Thyroid surgery should be done by experienced surgeon and care should be taken especially in huge goiters and patients undergoing total thyroidectomy. Keywords: Thyroidectomy; Recurrent laryngeal nerve; Injury; Prevalence; Recovery